Qubit state tomography in a superconducting circuit via weak measurements. (27th March 2017) - Qin, Lupei; Xu, Luting; Feng, Wei; Li, Xin-Qi
Abstract: In this work we present a study on a new scheme for measuring the qubit state in a circuit quantum electrodynamics (QED) system, based on weak measurement and the concept of weak value. To be applicable under generic parameter conditions, our formulation and analysis are carried out for finite-strength weak measurement, and in particular beyond the bad-cavity and weak-response limits. The proposed study is accessible to present state-of-the-art circuit QED experiments.